Electrical and optical properties of [poly[2-(3-1,2,3,4-tetrahydronaphtyl-3-methylcyclobutyl)-2-hydroxyethylmethacrylate] - Yakuphanoğlu, Fahrettin; Erol, I; Aydogdu, Y; Ahmedzade, M (Elsevier Science Bv, 2002)
The electrical and optical properties of newly synthesized polymer, poly[2-(3-1,2;3,4-tetrahydronaphtyl-3-methylcyclobutyl)-2-hydroxyethylmethacrylate (PTCHEMA), have been investigated. The results show that the sample has semiconducting behavior as its conductivity increases with increased temperature and the value of conductivity is order of magnitude (10(-6) S/cm). In addition, the thermal conductivity is measured in the investigated temperature range. Optical energy band gap and activation energy of the sample have been determined by means of optical spectra and electrical measurements, respectively. The study of the surface appearance of the sample is-done by means of electron scanning (SEM). (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: polymer; electrical conductivity; semiconducting